Kształtowanie kultury BHP skutecznym elementem systemu zarządzania - Boczkowska, Katarzyna; Niziołek, Konrad (Wydawnictwo Media Press, 2008)
The paper presents the results of its author's own research carried out in the small and medium size enterprises sector. It presents the analysis of safety evaluation of the organizational culture, in particular it describes selected activities of Polish organisations, the evidence of managerial professionalism, in health and safety management. It is most important of implementation systems based of Polish standards in the 18000 series.
Keywords: kultura bezpieczeństwa; zarządzanie przedsiębiorstwem; bezpieczeństwo i higiena pracy; security culture; business management; occupational health and safety